Development of fuel cell powered automotive thermal comfort and refrigeration system - Musa, Md. Nor (Faculty of Mechanical Engineering, 2007)
In a bus air conditioning system, the working load is relatively high in comparison to a passenger car. As such, the size of the compressor used is also relatively large due to high refrigerant flow rate required to meet the demand for high cooling capacity. For high refrigerant flow rate, reciprocating piston-cylinder concept has been known to operate successfully. The present work carried out is also based on the pistoncylinder compression concept but attempt was made to reduce the size of the compressor so that it is more compact and stable. This thesis reports the actual effort of introducing a novel concept of compression mechanism of the refrigerant compressor for a bus air conditioning system. The development of prototypes is based on experience and knowledge gained through reverse engineering on several existing compressor models in the market such as the swash plate compressor and the wobble plate compressor. Literature reviews were carried out to keep up with the latest technology that is available in the market and to acquire more state of the art knowledge required to design a better compressor. In parallel, an experimental rig was developed based on international standard to test and evaluate both existing and newly developed compressors. Tests were conducted by varying the compressor speed from 800rpm to 1800rpm. The performance of the compressors were studied in terms of coefficient of performance (COP), volumetric efficiency ( v Î·) and mechanical efficiency ( mech Î· ). For the existing compressor model, the highest COP obtained was 4.1 at 800rpm while the highest volumetric and mechanical efficiencies are 71% at 1400 rpm and 74% at 800 rpm. Similar data were planned to be obtained from the test of the newly developed prototypes. However, the new prototypes were not fully developed and data obtained from the test carried out were not enough to make a conclusive comparison with the performance of the existing model. The compressor managed to get a pressure ratio of 3 which was enough for an air conditioning system to work. The shortfalls and the source of the failure have been identified and recommendations for improvement have been made.